Anti-cyclic citrullinated peptide antibodies in hepatitis C virus associated rheumatological manifestations and Sjögren's syndrome. Issue 3 (10th February 2006) - Sène, D; Ghillani-Dalbin, P; Limal, N; Thibault, V; van Boekel, T; Piette, J-C; Cacoub, P
Abstract : Objective: To investigate the diagnostic reliability of anti-CCP antibodies (anti-CCP Ab) in distinguishing hepatitis C virus (HCV) associated rheumatological manifestations and Sjögren's syndrome from rheumatoid arthritis. Methods: 147 HCV infected patients (HCV RNA positive) were compared with 64 patients with definite rheumatoid arthritis in a retrospective study. Anti-CCP Ab were detected using the Immunoscan ELISA kit (second generation) and rheumatoid factor (RF) by the FIDIS™ Rheuma kit. Results: Among the 147 HCV infected patients (77 women; mean (SD) age 58 (16) years), 77 (52%) had a mixed cryoglobulin (MC), 38 (26%) an MC associated systemic vasculitis, 35 (24%) arthralgia/arthritis, and seven (5%) definite Sjögren's syndrome. HCV infected patients with arthralgia were more often RF positive than those without arthralgia (54% v 27%; p = 0.003), but less often than patients with rheumatoid arthritis (54% v 81%; p = 0.009). Anti-CCP Ab were detected in only two HCV infected patients with arthralgia (5.7%), in none without arthralgia or with Sjögren's syndrome, and in 78% of patients with rheumatoid arthritis. With a specificity of 93.5% and a positive predictive value of 96% for rheumatoid arthritis, anti-CCP Ab were the most specific biological marker. Conclusions: Anti-CCP antibodies are very rarely found in HCV infected patients with rheumatological manifestations or Sjögren's syndrome. They are reliable serological markers to distinguish these from patients with rheumatoid arthritis.